Soret and Dufour effects on MHD free convective flow past a vertical porous plate in the presence of heat generation - Reddy, Gurrampati Venkata Ramana (Zielona Góra: Uniwersytet Zielonogórski)
An MHD fluid flow is examined over a vertical plate in the presence of Dufour and Soret effects. The resulting momentum, energy and concentration equations are then made similar by introducing the usual similarity transformations. These similar equations are then solved numerically using the Runge-Kutta fourth order method with shooting technique. The effects of various parameters on the dimensionless velocity, temperature and concentration profiles as well as the local values of the skin-friction coefficient, the Nusselt number and Sherwood number are displayed graphically and in a tabular form. A comparison with previously published work is obtained and an excellent agreement is found.
Keywords: radiation; heat transfer; mass transfer; skin-friction; Nusselt number; Sherwood number